Economic Analysis Of Transfusion Dependent Thalassaemia (Tdt) And Deferasirox Fct Efficiency In Malaysia - Wong, Jacqueline Hui Yi (2020)
Thalassaemia is a common genetic disorder in Malaysia where the mainstay of supportive treatment is regular blood transfusion accompanied with iron-chelating therapy (ICT). Transfusion dependent thalassaemia (TDT) is defines as patient who requires blood transfusion >100mL/Kg annually. There are about 4500 patients in Malaysia who are suffering from TDT, however limited data is available on economic burden of this disease and also the efficiency of new formulated Deferasirox (Exjade FCT). Therefore, this study is designed to determine the economic burden of disease, cost effectiveness and budget impact of Exjade FCT in Malaysian context. Substudy one is to estimate the total lifetime cost of a TDT patient. Lifetime healthcare cost (TC2) was simulated using Markov model. Lifetime patient and family healthcare expenditure (TC3) was estimated through cross-sectional health survey approach. Survey was conducted using two-stage sampling method in 13 thalassaemia centers covering all regions in Malaysia. Total lifetime TDT cost (TC1) = TC2 + TC3. Substudy two to evaluate the cost effectiveness of Exjade FCT over the long standing gold standard treatment in TDT – Desferrioxamine. Costs and health outcome (quality adjusted life years) was estimated using Markov model. Costs data was extracted from local database and quality of life data was collected using EQ-5D-3L questionnaire among local thalassaemia patient. Lastly, substudy three, budget impact of converting the current oral ICT- Deferasirox dispersible tablet (Exjade DT) to Exjade FCT was evaluated using budget impact model.